2015
DOI: 10.1007/s10995-015-1827-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Continuum of Care Pathway for Maternal Health in South Asia and Sub-Saharan Africa

Abstract: Objective We assess how countries in regions of the world where maternal mortality is highest - South Asia and Sub-Saharan Africa - are performing with regards to providing women with vital elements of the continuum of care. Methods Using recent Demographic and Health Survey data from nine countries including 18,036 women, descriptive and multilevel regression analyses were conducted on four key elements of the continuum of care - at least one antenatal care visit, four or more antenatal care visits, deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

50
139
11
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(201 citation statements)
references
References 23 publications
50
139
11
1
Order By: Relevance
“…Autonomy in household decisions to seek health care, even if it did not show association with completion of CoC in this study, a number of studies found that it increases the probability of completion along continuum of care for MNH services. For instance, a 20% increase in Pakistan and 45% increase in south Asia and Sub-Saharan African countries was documented in previous studies [22,30]. The other implication to this finding is that working women might have more access to gain money and plan for health care unlike housewives who solely engage in household duties.…”
Section: Discussionmentioning
confidence: 64%
“…Autonomy in household decisions to seek health care, even if it did not show association with completion of CoC in this study, a number of studies found that it increases the probability of completion along continuum of care for MNH services. For instance, a 20% increase in Pakistan and 45% increase in south Asia and Sub-Saharan African countries was documented in previous studies [22,30]. The other implication to this finding is that working women might have more access to gain money and plan for health care unlike housewives who solely engage in household duties.…”
Section: Discussionmentioning
confidence: 64%
“…According to the World Health Organization (WHO), 2015 estimation approximately 303,000 maternal deaths occurred globally, most of the deaths occur during labor, delivery and the immediate postpartum period [2].For subsequent reduction of this problem the new globally adopted agenda between 2016 and 2030 as a part of sustainable development goal aimed to reduce maternal mortality ratio to 70 per 100,000 by addressing all maternal health care services for every woman as a top priority [4]. But women in most countries dropout before completing the full component of maternity continuum of care [3].In many countries, there is a significant dropout among women who had ANC visitbefore getting other subsequent maternal health care services [5,6]. This dropout or failure to access skilled birth attendants and postnatal care results for compromised health and wellbeing of both the mother and newborn [7].…”
Section: Introductionmentioning
confidence: 99%
“…412 Although many women attend at least one PNC visit, less than half complete the four recommended PNC visits or the 6-week postnatal visit. 13 …”
Section: Introductionmentioning
confidence: 99%